Clinical and Electrophysiological Effects of Downhill Treadmill Walking in Patients With Ischemic Stroke - Burak Yıldız; İpek Midi; Evrim Karadağ-Sayg; Özge Keniş-Coşkun (American Journal of Physical Medicine & Rehabilitation, 2026)
Objective: To evaluate the clinical and electrophysiological effects of downhill treadmill walking performed at different inclines in patients with stroke. Design: Thirty-five patients with stroke were randomized to level treadmill walking (control), −7.5% downhill walking, or −15% downhill walking. In this assessor-blinded trial, the intervention consisted of five sessions delivered over 5 consecutive days. Clinical outcomes assessed before and after the intervention were the Modified Ashworth Scale, Fugl-Meyer Lower Extremity Scale, 2-Minute Walk Test, Timed Up and Go Test, and Berg Balance Scale. The H-reflex maximum-to-M-wave maximum ratio was measured at baseline, after the first session, and after the final intervention session. The primary end point was the change in this ratio from baseline. Results: After a single session, the ratio decreased only in the −15% group. After five sessions, decreases were observed in the paretic leg in both the −7.5% and −15% groups, whereas no significant change was observed in the control group. The 2-Minute Walk Test and Timed Up and Go Test improved in all groups; these improvements were greater in the −15% incline group than in the level-walking control group. No significant changes were observed in the Modified Ashworth Scale or Berg Balance Scale scores. Conclusion: Downhill treadmill walking was associated with short-term modulation of spinal reflex excitability after stroke, suggesting that incline magnitude and repeated exposure may influence the electrophysiological response. Although the 2-Minute Walk Test and Timed Up and Go Test improved across all groups after five sessions, the greater improvements observed in the −15% incline group compared with the level-walking group suggest that a steeper downhill walking stimulus may be associated with greater early functional gains. However, these findings should be interpreted with caution given the short intervention duration, small sample size, and absence of follow-up assessments; therefore, their clinical significance and durability remain uncertain.